ANALISIS EFISIENSI PRODUKSI USAHATANI CABAI MERAH DI PROVINSI LAMPUNG - Lona, Nia Jessica; Rosanti, Novi; Saleh, Yuliana (Lampung University, 2025)
The aim of this research is to analyze technical efficiency and technical inefficiency, profitability and income of red chili cultivation businesses in Lampung province. This research was carried out in South Lampung and Pesawaran Regencies. Respondents were identified using a simple random sampling method from a total of 67 chili producers. Survey data was collected from October to December 2023. Technical efficiency and inefficiency were analyzed using the stochastic frontier method, efficiency was analyzed using the dual marginal cost function method, and agricultural productivity was calculated using agricultural income analysis. The research results show that red chili producers in Lampung Province are technically efficient, with an efficiency score 94.10%. Factors that influence the technical inefficiency of red chili cultivation are age, number of family members and farming experience. The profitability of growing chilies is less than 10%. The monetary income from cultivating red chilies in Lampung Province is IDR 29,595,410/0.28 ha and the R/C value of monetary costs is 3.3. Total income from red chili cultivation is IDR 26,203,341/0.28 ha with an R/C value of 2.5. It means that planting red chilies in Lampung Province is profitable. Keywords: Efficiency, farming, red chili